Vitamin D receptor and 1α-hydroxylase are highly expressed in lungs of mice infected with H9N2 avian influenza viruses. Issue 211 (July 2021) - Lian, Pengjing; Bai, Yu; Li, Jingyun; Wang, Hongyan; Niu, Xiaofei; Zhang, Zihui; Li, Hongru; Zhao, Lihong; Qiao, Jian
Highlights: Vitamin D signaling pathway was activated in lungs of mice infected with H9N2 virus. Vitamin D inactivating enzyme (24-hydroxylase) expression levels were not obviously changed in H9N2 viruses infected lungs. 25(OH)D3 treatment had little effect on H9N2 infection in mice. Abstract: The H9N2 avian influenza viruses infect poultry worldwide, and can potentially cause a human pandemic without adaptation. Vitamin D3 (D3) is increasingly being recognized for its extra-skeletal roles, such as the inflammatory and immune responses to infection. The aim of this study was to analyze the changes in vitamin D metabolizing enzymes and vitamin D receptor (VDR) in the lung tissues of mice infected with H9N2. The mice were intranasally inoculated with the appropriate dose of the virus, and various clinical indices were measured on days 3, 7, 14 and 21 post-infection. H9N2 infection significantly increased the expression levels of 1α-hydroxylase mRNA and protein, which is the activating enzyme of 25-hydroxyvitamin D (25(OH)D3 ), but had no significant effect on the 25(OH)D3 inactivating enzyme 24-hydroxylase, indicating that inactive D3 might be converted to its active form in the H9N2-infected lungs. Furthermore, a significant increase was also observed in the VDR mRNA and protein levels, suggesting enhanced responsiveness of the lung tissues to 1, 25(OH)2 D3 post H9N2 infection. In addition, daily 25(OH)D3 injection from day 2–14 post-infection did not affect the clinical signs, virus replication and cytokine (IL-1β and TNF-α) production in the lungs of the infected mice. Given that the biological effects of D3 rely on its activation, and the binding of 1, 25(OH)2 D3 to VDR in specific tissues, our findings provide novel insights into the possible role of vitamin D in the development and progression of influenza.